The Influence of Transformational Leadership on the Performance of MSMe Employees in Tangerang City - Kurniyanto, Cahya Adi Achir; Hamid, Nurdin Abdul; Sitorus, Morgan Nicolas; Baron, Baron; Shodiq, Muhammad Zacky Syauqy Ibnu (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the influence of transformational leadership on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in Tangerang City, considering the strategic role of MSMEs in the national economy and the importance of human resource performance in sustaining business operations. The research employed a quantitative approach with a causal associative design, using a survey distributed to 100 MSME employees selected through purposive sampling. Data were collected through structured questionnaires that passed validity and reliability testing and met classical assumption requirements. The findings show that all transformational leadership instrument items were valid and reliable, and the data were normally distributed. The simple regression results indicate that transformational leadership has a positive influence on employee performance, with a regression coefficient of 0.582. The t-test confirms that this influence is statistically significant, while the coefficient of determination reveals that 61.2% of the variation in employee performance is explained by transformational leadership. These results demonstrate that higher levels of transformational leadership lead to improved employee performance, particularly in work quality, productivity, and commitment. Overall, the study concludes that transformational leadership is an essential managerial factor that should be developed within MSMEs to enhance human resource performance and strengthen business competitiveness.